THE CORE OF LIFE AND LOVE BASED ON ISLAMIC STANDPOINTS OF “COLLEGE IN AMERICA” DRAMA SCRIPT (AN ISLAMIC LITERATURE STUDY) - Tawvicky Hidayat; Encung Encung; Nurul Hidayati (Reflektika, 2022)
AbstractThis article reveals the core of life and love values in “College in America” script drama portrayed by Lewis D. Eigen. and this article is to analyze the literary works. The main analysis in this article is to explain philosophical values in the drama script, which is containing two kinds of values, namely the core of life and the core of love. The main purpose of this article is an analysis of one of the literary works. The analyzing of this article is using Islamic perspectives. So that, first, the writer tries to find and analyze the philosophical values, and the second, it tries to combine and analyze it using the standpoint of Islam. Furthermore, because of this Islamic standpoint, in this article will be found many analysis by using Al-Quran. Al-Hadits and Ijma'. The writer chose "College in America" Portrayed by Lewis D. Eigen to be analyzed because this script contains many philosophical values of life and love, especially Islamic values. Especially for anyone who wants to take college abroad, this article is very useful. This script drama told the reader many philosophical values without any intention to give some advices, in other words, Lewis D. Eigen is genius because he shows Islam softly, gently, and easily.